Inhibition Activity Of Ethanolic Extract Of Ulva lactuca Against Staphylococcus aureus - emelda, emelda; Safitri, Eka Asriani; Fatmawati, Annisa (Brawijaya University, 2021)
Staphylococcus aureus (S. aureus) is a normal flora that can cause mild skin infections, one of which is acne. Commonly used chemical treatments are antibiotics such as Clindamycin. Continuous use of antibiotics can lead to resistance. Natural ingredients that are possible can inhibit the growth of bacteria. Treatment caused by S.aureus is Ulva lactuca Linn. (Green algae). This marine biota contains compounds that have the potential to be antibacterial, including triterpenoids, flavonoids, and saponins. This study aims to compare antibacterial activity of ethanolic extract of Ulva lactuca and Clindamycin against S. aureus bacteria. This type of research is an experimental laboratory. Ulva lactuca was extracted by maceration method using ethanol 96% solvent. Then carried out testing for antibacterial activity using the agar diffusion method by sump technique. The study was divided into 6 groups. One Clindamycin group and 5 treatment groups respectively with extract concentrations of 20%, 40%, 60%, 80%, and 100%. The test was carried out in 3 repetitions. Data analysis was processed by SPSS using the Kruskal-Wallis test to determine which groups had difference. The results showed that the ethanolic extract of Ulva lactuca was able to inhibit the growth of S. aureus bacteria with strong categories at concentrations of 20%, 40%, and 60%. Very strong category at 80% and 100% concentrations. The 100% concentration had the largest average inhibition zone diameter of 22 ± 0.577 mm which was not significantly different from Clindamycin with a significance value of 0.043 (p <0.05). This study concludes that the ethanolic extract of Ulva lactuca has activity in inhibiting the growth of S.aureus bacteria with strong to very strong categories, but statistically not as strong as Clindamycin